Disruptive innovations at the bottom of the pyramid : can they impact the sustainability of today´s top companies? - Baiyere, Abayomi (My University, 2011)
Due to the different dynamics required for organizations to serve the emerging market which contains billions of people at the bottom of the pyramid (BOP) coupled with the increasing desire for organizations to grow and be more multinational, organizations need to continually innovate. However, the tendency for large and established companies to ignore the BOP market and rather focus on existing markets, gives an indication of the existence of a vulnerability that potentially disruptive innovations from the BOP will not be recognized in good time for a counter measure. This can be deduced from the fact that good management practice advocates that managers should learn and listen to their customers. Therefore majority of the large existing companies continually focus on their main customer/market with sustaining innovations which leaves aspiring new entrants with an underserved BOP market to experiment with. With the aid of research interviews and an agent-based model (ABM) simulation, this thesis examines the attributes of BOP innovations that can qualify them as disruptive and the possibilities of tangible disruptive innovations arising from the bottom of the pyramid and their underlying drivers. The thesis Furthermore, examines the associated impact of such innovations on the future sustainability of established large companies that are operating in the developed world, particularly those with a primary focus which is targeted towards the market at the top of the pyramid (TOP). Additionally, with the use of a scenario planning model, the research provides an evaluation of the possible evolution and potential sustainability impacts that could emerge, from the interplay of innovations at the two pyramidal market levels and the chosen market focus of organizations – TOP or BOP. Using four scenario quadrants, the thesis demonstrates the resulting possibilities from the interaction between the rate of innovations and the segment focused on by organizations with disruptive era characterizing the paradigm shift quadrant. Furthermore, a mathematical model and two theoretical propositions are developed for further research. As recommendations, the thesis also extends the ambidextrous organizational theory, business model innovation and portfolio diversification as plausible recommendations to limit a catastrophic impact, resulting from disruptive innovations.